(untitled) (International Journal of Food and Nutritional Sciences, 2024)
In today’s digital age, shopping has become convenient and easy for people due to the rise of e-commerce. However, because of the dominance of the popular global e-commerce giants it has become difficult for local businesses to promote and sell their products effectively in the digital world. The proposed e-commerce shopping website will serve as a local online marketplace, which can help promote and sell the diverse range of products and services offered by local businesses so customers are encouraged to buy from the local businesses, and the economy of the local community is boosted which is the main goal of this e-commerce website.